2022
DOI: 10.1590/1518-8345.6222.3715
|View full text |Cite
|
Sign up to set email alerts
|

Fatores determinantes da exposição sexual ao HIV em adolescentes luso-brasileiros: uma análise de caminhos*

Abstract: Resumo Objetivo: analisar os efeitos diretos e indiretos de fatores determinantes da exposição sexual ao vírus da imunodeficiência humana entre adolescentes homens que fazem sexo com homens e as implicações para o cuidado em enfermagem. Método: estudo transversal, realizado com 578 adolescentes de 18 a 19 anos luso-brasileiros. Avaliaram-se inter-relações de situação conjugal, uso de aplicativos de relacionamento, prática de chemsex, desinformação, credibilidade do parceiro, práticas sexuais desafiadoras e m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Among the possible explanations for this, the awareness of risk, the desire to minimize or mitigate the possibility of infection associated with recurring bareback sex, and the previous history of other STIs may lead individuals to healthcare services, sensitizing them to the importance of this strategy, and motivating them to consider the use of PrEP as a preventive measure. 32 An unexpected finding in this study was that individuals with knowledge of PEP demonstrated a lower intention to use PrEP. Given that both are closely related prevention strategies, it was anticipated that familiarity with PEP would increase the intention to use PrEP.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Among the possible explanations for this, the awareness of risk, the desire to minimize or mitigate the possibility of infection associated with recurring bareback sex, and the previous history of other STIs may lead individuals to healthcare services, sensitizing them to the importance of this strategy, and motivating them to consider the use of PrEP as a preventive measure. 32 An unexpected finding in this study was that individuals with knowledge of PEP demonstrated a lower intention to use PrEP. Given that both are closely related prevention strategies, it was anticipated that familiarity with PEP would increase the intention to use PrEP.…”
Section: Discussionmentioning
confidence: 62%
“…56 However, the literature points out that partner trust can influence this perception of risk, leading some MSM who have high trust in their partners to adopt prevention measures with little or no effectiveness, such as interrupted coitus, questioning the history of STIs, relying on the partner's physical appearance, or asking about serological status. 30,32 In addition, there is evidence that indicates that, although chemsex occurs more frequently with casual partners, these partners are not always unknown. 11,34,60 This is due to the greater difficulty in finding partners who share the same type of drug for sex, which can create a sense of closeness and trust even with casual partners.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations